Radiological Control of the Floating Mass Transducer Attached to the Round Window - Ingo Todt; G. Rademacher; J. Wagner; P. Mittmann; Dietmar Basta; Arne Ernst (The Scientific World Journal)
The surgical rehabilitation of mixed hearing losses can be performed by coupling the floating mass transducer of the Vibrant Soundbridge to the round window. The quality of coupling the floating mass transducer to the round window is crucial for the audiological outcome. It was the aim of this study to further observe the different patterns of floating mass transducer position at the round window. We compared twenty patients with mixed hearing loss implanted with a floating mass transducer attached to the round window and 24 surgeries between 5/2007 and 6/2010. An evaluation of the chronological observation of the flat panel angiography-controlled position of the floating mass transducer at the round window with relation to the surgical report and the audiological outcome was done. We observed no changes in the mean pre- and postbone conduction thresholds. The floating mass transducer position was variable and could be radiologically classified and correlated with the audiologically outcome. A learning curve was observed from the earlier to later implantations. Postoperative, radiological evaluation of the location and angle of the floating mass transducer by means of flat panel tomography allowed us to classify the floating mass transducer position at the round window into 4 groups.